Effectiveness of Pelvic Floor Exercises on Urinary Incontinence in Urology Surgery Patients: Systematic Review - Asroful Hulam Zamroni; Elvi Kurnia Damayanti; Johanes Eban B. Dorman; Rizki Nur Azhadin; Ika Yuni Widyawati (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Urological surgery is a medical procedure in treating disorders of the urinary tract, reproductive organs, and other urogenital systems that have the most common risk of complications in the form of urinary incontinence. This systematic review aimed to assess the effectiveness of pelvic floor exercises are in reducing the occurrence of urinary incontinence among patients who have undergone urological surgery. Four databases, including Scopus, PubMed, ProQuest and Sciencedirect, were reviewed for relevant articles published from 2020 to 2025. The literature search was conducted using keywords such as "Pelvic-Floor-Exercises AND Urinary-Incontinence AND Post-Urology-Surgery". Guidelines from the Joanna Briggs Institute were used to assess the quality of journals reviewed. Articles were analyzed by extracting data in the form of country, type of study, sample, age, gender, intervention (type and duration), instrument, and outcome. Seven randomised controlled clinical trials (RCTs) involving 422 articles were included. All studies reported a significant decrease in urinary incontinence after Kegel exercises (p 0.05). Research indicates that engaging in pelvic floor exercises can enhance the strength of pelvic floor muscles, leading to better bladder control and a decrease in the occurrence of urinary incontinence. Pelvic Floor Exercises can be part of a urological post-operative recovery program that supports the patient's overall recovery and quality of life. Nurses can teach and motivate patients to perform pelvic floor exercises according to the patient's progress and condition. The results lay a strong groundwork for application in clinical settings, and further studies are necessary to establish a standardized protocol and investigate its long-term effects.